Flow Chart. - Jason Shourick (11436869) (2025)
Objective To ascertain whether, in comparison to the participants’ expected abilities, the weather may cause abnormally poor cognitive or physical performance. Design Secondary analysis of a randomised controlled trial Setting Study conducted between May, 2008, and Feb, 2011 in 13 memory centres in France and Monaco Participants 1313 participants from the MAPT trial, a 5-year multicentre prevention trial, which included dementia-free individuals aged over 70 years. Participants presented subjective memory complaints, slow gait speed and/or an instrumental activity of daily living limitation. Main outcome measures Cognition was assessed using a composite cognitive Z-score (composed of digit symbol substitution test, free and cued selective reminding test, Mini-mental state, category fluency) and subjective memory complaints. Physical function was assessed using gait speed, the short physical performance battery (SPPB) and its components, and grip strength. Abnormally low scores were defined as an observed score that was lower than the individual’s expected ability by at least the minimal clinically important difference. Results Higher outdoor temperature was associated with a significantly increased risk of abnormally low gait speed or SPPB (respectively OR 1.13 95% CI (1.04, 1.22) and OR 1.15 95% CI (1.03, 1.29) for 10 degrees Celsius), but did not significantly increase the risk of abnormally low cognitive function. Conclusion Our results suggest that weather conditions should be strongly considered when assessing the physical performance of older adults in the context of clinical practice and clinical research as examination in hot weather might lead to false conclusions on the participants’ abilities.